Collision avoidance method for unmanned ships using a modified APF algorithm - Li, Lianbo; Wu, Wenhao; Li, Zhengqian; Wang, Fangjie (Frontiers in Marine Science, 2025)
The Artificial Potential Field (APF) algorithm has been widely used for collision avoidance on unmanned ships. However, traditional APF methods have several defects that need to be addressed. To ensure safe navigation with good seamanship and full compliance with the Convention on the International Regulations for Preventing Collisions at Sea, 1972 (COLREGS), this study proposes a dynamic collision avoidance method based on the APF algorithm. The proposed method incorporates a ship domain priority judgment encounter situation, allowing the algorithm to perform collision avoidance operations in accordance with actual operational requirements. To address path interference and unreachable target issues, a new attractive potential field function is introduced, dividing the attractive potential field of the target point into multiple segments simultaneously. Additionally, the repulsive force on the own ship is reduced when close to the target point. The results show that the proposed method effectively resolves path oscillation problems by integrating the potential field based on traditional APF with partial ideas from the Dynamic Window Approach (DWA). In comparison with traditional APF algorithms, the overall smoothing degree was improved by 71.8%, verifying the effectiveness and superiority of the proposed algorithm.